Ustavnosodna presoja mednarodnih pogodb - Škrk, Mirjam (Revus (Ljubljana), 2006)
Treaties form an indispensable part of the contemporary international law. As a result of states' sovereignty, there exists a very high degree of autonomy of parties in the field of concluding treaties. However, the pacta sunt servanda principle is one of the most eminent principles of international law. Accordingly, the breach of a treaty entails the responsibility of states. A substantial number of democratic constitutions, including the Constitution of the Republic of Slovenia, recognize the supremacy of international law over the domestic law. Despite this fact, looking from the perspective of the internal legal order, the national constitution must be assigned the nature of the supreme legal act. The same applies to the Constitution of the Republic of Slovenia. The purpose of the constitutional review of treaties is to prevent an unconstitutional treaty commitment from becoming part of the domestic legal order. According to the second paragraph of its Article 160 (Powers of the Constitutional Court), the Slovenian Constitution regulates the preventive (a priori) constitutional review of treaties only. On the proposal of the President of the Republic, the Government or a third of the deputies of the National Assembly, the Constitutional Court issues an opinion on the conformity with the Constitution of a treaty which is in the process of ratification. The National Assembly is bound by such opinion. In the event the Constitutional Court establishes that there exists an unconstitutional provision of a treaty, the National Assembly must not ratify it. Should the Constitutional Court decide that the treaty is in conformity with the Constitution, it rests within the political domain of the National Assembly to ratify such treaty or not. The Constitutional Court has delivered four opinions on the preventive constitutional review of treaties. These opinions were used as the basis for the analysis of selected constitutional and international legal issues that have emerged during the review of the Constitutional Court. In addition, on the basis of its case-law the Constitutional Court has also established the indirect (a posteriori) constitutional review of treaties. It has done so by reviewing the act of ratification that serves as a form for the adoption of a treaty in the domestic legal order. The Constitutional Court decided on merits just in one such case. It decided that a governmental decree on the ratification of an international agreement was not unconstitutional. Other petitions were rejected or found manifestly ill-founded. On the basis of the case-law of the Constitutional Court the conclusion has been made that the preventive (a priori) constitutional review of treaties has proved to be a more effective legal remedy for reviewing the constitutionality of treaties than the a posteriori review. The latter demands a certain degree of restraint by the Constitutional Court due to the fact that an already binding treaty is concerned. Notably, it is not within the powers of the Constitutional Court to create any effects towards other parties to the treaty. The state is bound to fulfill the treaty in good faith despite the fact that the Constitutional Court has eventually established that some of its provisions are unconstitutional, otherwise it commits an international delict.
Keywords: mednarodne pogodbe; mednarodno pravo; presoja ustavnosti; ustavna sodišča